UX information in the daily work of an agile team: A distributed cognition analysis. Issue 147 (March 2021) - Zaina, Luciana A.M.; Sharp, Helen; Barroca, Leonor
Highlights: Ethnographic study of agile team using novel analytic lenses suggests guidelines for UX practice Agile team members consume UX information rather than produce it Predominance of information about user interaction rather than user goals Information about the user perspective is communicated verbally and not captured in artefacts Complex UX information flow indicates potential communication breakdown Abstract: The integration of agile software development and user experience (UX) design has been a topic of investigation for practitioners and researchers for many years, and agile teams have become increasingly aware of the importance of UX design. Most studies have focused so far on the integration of UX theories and methods with agile practices. The objective of this research is to investigate whether and how UX information is embedded in the daily work of an agile team. We conducted an ethnographic study of an agile team based in the UK. We performed a qualitative analysis using different data sources and three complementary analytical lenses: Distributed Cognition of Teamwork, Garrett's set of UX elements and planes, and Hassenzahl's content-oriented model of UX. This combination provided an understanding of the different types of UX information available to the agile team through artefacts and face-to-face meetings, how the information flowed within and around the agile team, and the type of engagement they have with UX information. The findings reveal that: (1) agile team members were consumers of UX information not producers; (2) the most common type of UX information found in the system related to how the user interacts with the product rather than to user goals or needs; (3) information focusing on the user perspective appears in verbal communication rather than being captured in artefacts; and, (4) the flow of UX information around the team is complex. In combination, these factors indicate a potential breakdown in the communication of UX information. We argue that these findings have relevance for other agile teams because the artefacts and methods used by this team are commonly used by other agile teams. To improve the situation, we suggest a number of recommendations to engage agile team members in UX work, and reduce the complexity of UX information flow.